Surasundari - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel has an apsara (celestial nymph) or surasundari (young girl as a symbol of graceful beauty) framed between two pillars decorated with yalis and other mythical creatures. The female figure may be an apsara (celestial nymph) or surasundari (young girl as a symbol of graceful beauty) standing in the tribhanga pose (triple-bend). She holds a darpana (mirror) in her left hand and the free end of a dupatta-like garment wrapped around her arms, back, and shoulder in her right hand. While the face is badly damaged, the headgear and hoop earrings are still discernible. Among the various ornaments she is wearing, is a pendant hanging till the navel and two leaf-shaped pendants hanging from chains attached to the katibandha (decorative belt) around her waist.